Proceedings of the 27th Workshop on Network and Operating Systems Support for Digital Audio and Video 2017
DOI: 10.1145/3083165.3083167
|View full text |Cite
|
Sign up to set email alerts
|

Improving Video Quality in Crowded Networks Using a DANE

Abstract: Dynamic Adaptive Streaming over HTTP (DASH) is a technology for delivering video content over the Internet. It provides an e ective mechanism, which has been adopted by major content providers. Nevertheless, available DASH player implementations have a number of drawbacks such as performance problems on shared network connections, which lead to video freezes and frequent video quality changes. In this paper, we propose a method to reduce the performance problems that exist in networks with a large number of DA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…In MPEG-DASH SAND, we find the coupling of network assistance with coordination from the client. In fact, the network has a general view and can provide bandwidth reservation at routers, clients are in charge of the final decision and can receive recommendations [21] [22] [23].…”
Section: Related Workmentioning
confidence: 99%
“…In MPEG-DASH SAND, we find the coupling of network assistance with coordination from the client. In fact, the network has a general view and can provide bandwidth reservation at routers, clients are in charge of the final decision and can receive recommendations [21] [22] [23].…”
Section: Related Workmentioning
confidence: 99%
“…In extensive evaluations in a Wi-Fi testbed it was demonstrated that our DANE outperforms state-of-the-art DASH adaptation algorithms [7,8]. The performance of DANEs in large networks (up to 600 players) was investigated in [12].…”
Section: Status and Outlookmentioning
confidence: 99%
“…In a crowded network our DANE effectively eliminates freezes, increases video bitrate, reduces quality switches, and establishes fairness (as in bitrate). In [22], the scalability of the out-of-band DANE is enhanced. To be able to cope with a large number of frequently starting and stopping DASH players, the transactions between DANE and DASH players, as well as between DANE and network switch are reduced.…”
Section: Dash Assisting Network Elementmentioning
confidence: 99%
“…[16,18,20,22]) and journals (i.e [17,19,21]). A timeline overview of the contributions with corresponding papers is given in Figure 2.…”
Section: Status and Outlookmentioning
confidence: 99%
See 1 more Smart Citation